Mitigation of Learned Helplessness for Enhanced Bureaucratic Organizational Responsiveness in Public Administrations - Niva Dolev; Liza Ireni-Saban (Administrative Sciences)
Organizational bureaucratic responsiveness, the readiness and ability of public organizations to respond to public needs, in particular in times of change, requires collaborations between public organizations and citizens and responsiveness to citizens’ evolving needs. One of the organizational barriers to such collaborations may be learned helplessness (LH), the belief that actions and outcomes are unrelated and a lack of sense of control. However, the relationship between the two in the framework of public organizations in current times has been little examined. This paper proposes a novel theoretical framework for collaborative responsiveness that builds on a process-based approach and thereby indicates the potential impacts of LH on collaborative responsiveness in public organizations, particularly in current times when it is most needed. Practical ways for mitigating learned helplessness and supporting collaborative responsiveness in changing times are suggested.